Journal of Malaysian Branch of the Royal Asiatic Society (JMBRAS) 1987-1996: a Ten-Year Bibliometric Analysis - Tiew, W.S. (Masters of Library of Inf. Sci. Program Uni. of Malaya, 1998)
Describes and analyses key bibliometric components of articles and book reviews published in the Journal of the Malaysian Branch of the Royal Asiatic Society (JMBRAS) between 1987-1996